Reações de impulso em mecanismo articulado plano com folga nas articulações - Rosa, Juarez (1973)
The dynamic performance of a four-bar plane linkage with clearance in one of the revolutes is investigated. Impulsive reactians at the joints were evaluated during impact and free flight modes. External and inertia loads are accounted for. The analysis was applied to a similar linkage witha out clearances, for camparisan purposes. Digital programs were prepared for both phases of research, and numerical examples are presented. Sections (2.5) and (2,6) regarding the "PROXIMITY PERTURBATIDN" method and all the contents of chapter III are new cantributions to the area af mechanisms.